2009
DOI: 10.1016/j.nuclphysa.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A microscopic three-cluster model with nuclear polarization applied to the resonances of 7Be and the reaction 6Li(p, 3He)4He

Abstract: A microscopic model for three-cluster configurations in light nuclei is presented. It uses an expansion in terms of Faddeev components for which the dynamic equations are derived. The model is designed to investigate binary channel processes in a compound system. Gaussian and oscillator bases are used to expand the wave function and to represent appropriate boundary conditions. We study the effect of cluster polarization on ground and resonance states of 7 Be, and on the astrophysical S-factor of the reaction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 62 publications
(151 reference statements)
3
56
0
Order By: Relevance
“…The screening effects are also not included in the calculations [9,10]. The results of these works qualitatively agree with each other and with ours but all three calculations differ quantitatively from each other at low energies.…”
Section: Discussion Of the Results Conclusionsupporting
confidence: 81%
See 2 more Smart Citations
“…The screening effects are also not included in the calculations [9,10]. The results of these works qualitatively agree with each other and with ours but all three calculations differ quantitatively from each other at low energies.…”
Section: Discussion Of the Results Conclusionsupporting
confidence: 81%
“…The results of these works qualitatively agree with each other and with ours but all three calculations differ quantitatively from each other at low energies. The calculation [10] gives the largest overestimation of the data compared to the others.…”
Section: Discussion Of the Results Conclusionmentioning
confidence: 84%
See 1 more Smart Citation
“…Second, in our recent works [38,39], we formulated a microscopic three-cluster model which was specially designed to consider the polarizability of interacting clusters. We called it the cluster polarization.…”
Section: Introductionmentioning
confidence: 99%
“…In our early works [40][41][42], we demonstrated that the collective monopole and quadrupole polarizations have very large effects on the radiative capture and photodisintegration reactions. Here, we consider a more important and prominent type of polarization, as it was shown in [38,39]. As in [38,39], we will use the three-cluster configuration 4 He + d + p ( 4 He + d + n) to consider the binary channels 4 He + 3 He and 6 Li + p ( 4 He + 3 H and 6 Li + n) in 7 Be ( 7 Li).…”
Section: Introductionmentioning
confidence: 99%